Fairness, QoS, and buffer sizing. - Wischik, Damon
This note is a reply to some of the points about buffer sizing raised by Dhamdhere and Dovrolis [1]. I'll use a simple mathematical model to make stark some of the tradeoffs that need to be weighed when deciding on buffer size.
Keywords: Computer systems organization; Performance of systems; Reliability, availability and serviceability; Computer communication networks; Network operations; Network management; Operating systems; Software; Communications management; Buffering; Performance; Reliability; Theory